2018
DOI: 10.18632/oncotarget.24130
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization of multidrug-resistant cancer cells to Hsp90 inhibitors by NSAIDs-induced apoptotic and autophagic cell death

Abstract: NSAIDs (non-steroidal anti-inflammatory drugs) have potential use as anticancer agents, either alone or in combination with other cancer therapies. We found that NSAIDs including celecoxib (CCB) and ibuprofen (IBU) significantly potentiated the cytotoxicity of Hsp90 inhibitors in human multidrug-resistant (MDR) cells expressing high levels of mutant p53 (mutp53) protein and P-glycoprotein (P-gp), and reversed Hsp90 inhibitor resistance caused by activation of heat shock factor 1 (HSF1) and by up-regulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 46 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…Recently, Mcl-1, a downstream target of STAT3, has been reported to have an important role in the regulation of autophagy, and the degradation of Mcl-1 relieves Beclin-1 50,51 , indicating that STAT3/Mcl-1 pathway is also involved in regulation of autophagy. Previously, we also reported that autophagy inducing the ability of NSAIDs through inhibition of Akt/mTOR and STAT3 pathways was effective for the sensitization of MDR cells to 17-AAG 52 . Similarly, the current study showed that activation of AMPK and inhibition of Akt/mTOR/p70S6K/4EBP1 signaling axis and STAT3/Mcl-1 pathways participate in NSAID-induced autophagy in CD44 high K562 cells.…”
Section: Discussionmentioning
confidence: 81%
“…Recently, Mcl-1, a downstream target of STAT3, has been reported to have an important role in the regulation of autophagy, and the degradation of Mcl-1 relieves Beclin-1 50,51 , indicating that STAT3/Mcl-1 pathway is also involved in regulation of autophagy. Previously, we also reported that autophagy inducing the ability of NSAIDs through inhibition of Akt/mTOR and STAT3 pathways was effective for the sensitization of MDR cells to 17-AAG 52 . Similarly, the current study showed that activation of AMPK and inhibition of Akt/mTOR/p70S6K/4EBP1 signaling axis and STAT3/Mcl-1 pathways participate in NSAID-induced autophagy in CD44 high K562 cells.…”
Section: Discussionmentioning
confidence: 81%
“…Monotherapy and combinatory therapy with COX inhibitors have been reported in the treatment of various types of cancers. Cell cycle progression, migration, invasion, angiogenesis, autophagy, apoptosis, and resistance can be classified as biochemical events that are vulnerable to either direct or indirect actions of COX inhibitors [ 4 , 5 , 6 , 7 , 8 ]. While COX inhibitors appear to induce adverse effects and off-target actions, they also display chemo-preventive properties that warrant further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Under strong cellular ER stress, NSAID-induced autophagy results in induction of apoptosis. [75][76][77][78] Dimethyl celecoxib, a derivative of celecoxib, effectively inhibits colon cancer, triple-negative breast cancer, and glioma cell growth through induction of ER stress and in combination with chloroquine, bortezomib, and radiotherapy to play synergic effects on the induction of tumor cell autophagy. 79,80 Celecoxib targets the pro-oxidative state of highly metastatic cancer cells and cancer stem cells and drives excess ROS production in these cells, resulting in cell death.…”
Section: Celecoxib and Its Derivativesmentioning
confidence: 99%
“…94 Furthermore, sulindac sulfide increased the sensitivity of multidrug-resistant cancer cells to Hsp90 inhibitors through the induction of autophagy. 75 Sodium salicylate inhibited the growth of A549 cells through the transformation from tumor necrosis to tumor-suppressive autophagy. 95 Moreover, Bauvy et al reported that inhibition of autophagy increased sulindac sulfide-induced apoptosis in HT-29 cells.…”
Section: Sulindac Sulfidementioning
confidence: 99%